2019
DOI: 10.1111/are.14208
|View full text |Cite
|
Sign up to set email alerts
|

Early development and allometric growth in hatchery‐reared Eurasian perch, Perca fluviatilis L.

Abstract: The morphological development and allometric growth patterns of Eurasian perch, Perca fluviatilis L., a highly valued commercial species, were studied under intensive rearing conditions from hatching up to 50 DPH (Days Post Hatch). Based on the external morphology, four different phases during early development of Eurasian perch were identified: pre‐flexion larva 0–20 DPH (5.70–10.16 mm TL); flexion larva 22–30 DPH (11.09–15.14 mm TL) and post‐flexion larva/juvenile 32–50 DPH (18.00–24.75 mm TL). The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
5
6
0
Order By: Relevance
“…Overall, the growth patterns (in terms of weight and length) observed in the larvae under investigation are consistent with other experiments on Eurasian perch [10, 30]. Additionally, there were no major differences observed in cannibalism behavior and swim bladder inflation rate when compared to a previous study that exposed the larvae to similar experimental conditions [10, 30]. Additionally, larval mortality was mostly determined by problems related to nonfeeding behavior after the oil droplet reduction stage, cannibalism and problems with swim bladder inflation [10, 28, 31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, the growth patterns (in terms of weight and length) observed in the larvae under investigation are consistent with other experiments on Eurasian perch [10, 30]. Additionally, there were no major differences observed in cannibalism behavior and swim bladder inflation rate when compared to a previous study that exposed the larvae to similar experimental conditions [10, 30]. Additionally, larval mortality was mostly determined by problems related to nonfeeding behavior after the oil droplet reduction stage, cannibalism and problems with swim bladder inflation [10, 28, 31].…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the growth patterns (in terms of weight and length) observed in the larvae under investigation are consistent with other experiments on Eurasian perch [10, 30]. Additionally, there were no major differences observed in cannibalism behavior and swim bladder inflation rate when compared to a previous study that exposed the larvae to similar experimental conditions [10, 30].…”
Section: Discussionsupporting
confidence: 88%
“…This also partially explains the compensation of expression of the genes at the whole organism level observed at the end of the study. It has been reported that the eyes in Eurasian perch at hatching are constituting significant component of the entire body, as the visual system is crucial for survival of the larvae 52 . Later the eyes are not growing anymore so rapidly as the rest of the body, especially the organs reponsible for the digestion.…”
Section: Discussionmentioning
confidence: 99%
“…In other species, however, the inflexion points are distributed along a wide TL interval like in A. baeri , in which the inflexion points were described in the TL interval of 10.5 to 29.1 mm (Gisbert, 1999). In other species, however, most of the inflexion points occurred at the end of the larval period like in P. fluviatilis , (Kupren et al ., 2019) in which the authors considered it as an indication of a gradual change in the body shape of the larvae probably related to the lack of severe changes in behaviour or habitat during the larval life.…”
Section: Discussionmentioning
confidence: 99%
“…The allometry during larval period has been described in many species, including freshwater species like the golden dwarf cichlid Nannacara anomala Regan, 1905 (Kupren, Prusińska, et al ., 2014), the burbot Lota lota (L. 1758) (Kupren, Trabska, et al ., 2014), the catfish Lophiosilurus alexandri Steindachner, 1876 (Guimaraes de Mello et al ., 2015), the Eurasian perch Perca fluviatilis (L. 1758) (Kupren et al ., 2019); anadromous like the Siberian sturgeon Acipenser baeri Brandt, 1869 (Gisbert, 1999), catadromous like Anguilla japonica Temminck and Schlegel 1846 (Shin et al ., 2022); and marine species similar to the Pacific red snapper, like the spotted sand bass Paralabrax maculatofasciatus (Steindachner, 1868) (Peña & Dumas, 2009), the common dentex Dentex dentex (L. 1758) (Koumoundouros et al ., 1999) and the California halibut Paralichthys californicus (Ayres, 1859) (Gisbert et al ., 2002). In all the species the same growth pattern has been reported: a high allometric growth of head and tail sections during the early larval stages and a posterior reduction in allometry and a clear tendency to isometric growth during the end of the larval period (Fuiman, 1983).…”
Section: Introductionmentioning
confidence: 99%